Efficacy of Conversion Surgery Following Apatinib Plus Paclitaxel/S1 for Advanced Gastric Cancer With Unresectable Factors: A Multicenter, Single-Arm, Phase II Trial - Xu, Zhiyuan; Hu, Can; Yu, Jianfa; Du, Yian; Hu, Ping; Yu, Guofa; Hu, Conggang; Zhang, Yu; Mao, Wei; Chen, Shanqi; Cheng, Xiangdong (Frontiers in Pharmacology, 2021)
Objective: Conversion therapy (surgical resection after chemotherapy) is a promising option for unresectable gastric cancer (GC) patients. Addition of anti-angiogenesis drug improves response to chemotherapy. Hence, this study explored the feasibility and efficacy of preoperative paclitaxel (PTX)/S1 chemotherapy combined with apatinib for unresectable GC. Methods: Thirty-one eligible patients with a single unresectable factor were enrolled in this multi-center, single-arm trial. Apatinib (500 mg qd) was administered continuously, while PTX (130 mg/m2) on day 1 and S1 (80 mg/m2) on day 1–14 were given every 3 weeks. The treatment was given for three cycles preoperatively, but the last cycle did not include apatinib. The primary objective measurements included R0 resection rate, objective response rate (ORR) and morbidity of preoperative treatment. Results: Among the 31 patients, 30 patients were evaluable for tumor response, the ORR to preoperative treatment was 73.3%. Eighteen of 30 patients underwent surgery, and R0 resection was achieved in 17 patients. The patients who underwent the conversion surgery had a superior OS compared with those who did not (3 years OS: 52.9 vs 8.3%, p = 0.001). The surgery was operated after apatinib had stopped for a median duration of 4 weeks. Neither anastomotic leakage nor wound healing complications was observed. No increased bleeding event was observed compared with historical data. During preoperative treatment, grade 3 or 4 toxicities were experienced by 58.1% of the patients. Conclusion: Chemotherapy in combination with apatinib demonstrated higher rates of conversion and R0 resection and a superior survival benefit in initial unresectable GC. It is safe and reasonable to suspend apatinib for 4 weeks before the gastrectomy.